Experimental investigation on wind uplift capacity of single span Z-purlins supporting standing seam roof systems. (November 2019) - Luan, Wei; Li, Yuan-Qi
Abstract: A total of 20 specimens of single-span purlin roof assemblies considering uplift wind load were tested to investigate the structural behavior of cold-formed steel Z-purlins having the tension flange fastened to standing seam roof systems. The variables of the tests include the type of standing seam roof systems, purlin thickness, purlin height and location of sag rods. Failure modes and flexural strengths of Z-purlins with and without sag rods were obtained from the tests. The test results were also compared with the flexural strengths calculated according to the Chinese code and North American specification, respectively. Furthermore, full finite element models representing the test specimens were then developed and nonlinear analysis was performed. The test results were in good agreement with the finite element analyses in terms of failure loads, failure modes and load-displacement curves. Highlights: Z-purlins supporting standing seam roof systems were tested under simulated wind uplift load. Failure modes of single span Z-purlins with and without sag rods were investigated. Test results were compared with the flexural strengths calculated according to AISI S100 and GB50018. FE models were developed to validate the test results.